M. Nel, Identity-driven churches: Who are we and where are we going? - A. R. Tucker (Acta Theologica)
From text: I have no hesitation in recommending this book for study by every minister, pastor, priest, bishop, denominational executives, “apostle”, and church leader in South Africa. In fact, I suggest that it become an essential tool in helping leaders develop missional churches. It is not always an easy read, but neither is it obscure, being clearly written, calling for a thoughtful and systematic study that produces a wealth of contextual biblical ideas concerning building up the local congregation in the present world. Why am I so enthusiastic in my recommendation?